ANALISIS EFISIENSI TEKNIS USAHATANI BAWANG PUTIH DESA NUNLEU KECAMATAN AMANATUN SELATAN KABUPATEN TIMOR TENGAH SELATAN - Bere, Yohana Balok; N Nalle, Mardet; M Fallo, Yosefine (Agros Journal of Agriculture Science, 2024)
This research aims to: (1) To determine the technical efficiency value of garlic in Nunleu Village, South Amanatun District, South Central Timor Regency; (2) To determine the value of the effect of Garlic Technical Inefficiency in Nunleu Village, South Amanatun District, South Central Timor Regency. Location in Nunleu Village, South Amanatun District, South Central Timor Regency, in August – February 2023. The sample was taken using simple random sampling, namely 60 KKT out of a total of 200 KKT. The research results show that the average technical efficiency value for garlic in Nunleu Village, South Amanatun District, North Central Timor Regency is 0.89, meaning that garlic farming has achieved technical efficiency. Factors that influence garlic production are land area, seeds, fertilizer, while labor has no influence on garlic production in Nunleu Village. Based on the Gamma value, it shows that 83 percent captures the effects of inefficiency from internal factors such as age, number of dependents, level of education and experience, while 17 percent is influenced by external factors such as climate and disease. Factors that influence technical inefficiency are age, number of dependents, level of education while experience does not capture the effect of technical inefficiency of Bwang Putih farming in Nunleu Village, South Amanatun District, South Central Timor Regency. Key words: Garlic, Efficiency, Timor Tengah Selatan INTISARIPenelitian ini bertujuan untuk: (1) Untuk Mengetahui Nilai Efisiensi Teknis Bawang putih di Desa Nunleu kecamatan Amanatun Selatan Kabupaten Timor Tengah Selatan; (2) Untuk Mengetahui nilai efek Inefisiensi Teknis Bawang Putih di Desa Nunleu Kecamatan Amanatun Selatan Kabupaten Timor Tengah Selatan. Lokasi Di Desa Nunleu Kecamatan Amanatun Selatan Kabupaten Timor Tengah Selatan, Pada Bulan Agustus – Februari 2023.Sampelnya diambil secara simple random sampling yaitu sebesar 60 KKT dari jumlah 200 KKT. Hasil penelitian menunjukkan bahwa rata-rata nilai efisiensi teknis bawang putih di Desa Nunleu Kecamatan Amanatun Selatan Kabupaten Timor Tengah Utara 0,89 berarti usahatani bawang putih telah mencapai efisiensi teknis. Faktor-faktor yang berpengaruh terhadap produksi bawang putih adalah luas lahan, bibit, pupuk sedangkan tenaga kerja tidak berpengaruh terhadap produksi Bawang Putih di Desa Nunleu. Berdasrkan nilai Gamma menunjukkan bahwa 83 persen menangkap efek inefiesiensi dari faktor internal seperti umur, jumlah tanggungan, tingkat pendidikan, dan pengalaman sedangkan 17 persen dipengaruhi oleh faktor eksternal seperti iklim dan penyakit. Faktor-faktor yang mempengaruhi inefesiensi teknis adalah umur, jumlah tanggungan, tingkat pendidikan sedangkan pengalaman tidak menangkap efek inefisiensi teknis usahatani Bwang Putih di Desa Nunleu Kecamatan Amanatun Selatan Kabupaten Timor Tengah Selatan.   Kata kunci: Bawang Putih, Efisiensi, Timor Tengah Selatan